Comparative study on aedes albopictus (Skuse) (diptera: culicidae) for the effects of temperature on development times and survivorship using field and laboratory strain / Natasha Shafeez Shamsusah - Shamsusah, Natasha Shafeez (2015)
In tropical areas where mosquito populations are particularly abundant, temperature is considered as one of the important factors in influencing the mosquito dynamics. This study was conducted to investigate the effects of water temperature on the egg-hatching, development times and wing length of Aedes albopictus under laboratory conditions using temperature regulated water baths of 28°C, 30°C, 32°C and 34°C. Two strains of Aedes albopictus were used in this study: (1) field strain: Aedes albopictus collected from Subang Jaya and (2) laboratory strain: Aedes albopictus obtained from Vector Control Research Unit (VCRU), Universiti Sains Malaysia (USM). Both strains were subjected to standard laboratory hatching procedures. Hatching rates of both strains were determined as the percent of eggs hatched to first instar after 48 hours. The mean hatching rate for laboratory strain decreased with increasing of temperature ranging from 83.3% at 28°C, followed by 38.7% at 30°C, 22% at 32°C and 16.70/0 at 34°C. Similarly, field strain 'also demonstrated the same reduction pattern for eggs hatching with 48%, 16.50/0, 5.8% and 0% at 28°C, 30°C, 32°C and 34°C respectively. Hatching rate of both strains was significantly higher under lower temperature (laboratory strain; p=O.027 and field strain; p=0.003) suggesting that temperature maybe an egg hatching stimulation factor. As for the duration of development from the first instar to adult, it was found to be inversely related to temperature with 9.7 days (28°C), 10.3 days (30°C), 11.3 days (32°C) and 12 days (34°C) for laboratory strain. Meanwhile, duration of development for field strain were 8.8 days at 28°C and 9.8 days at 30°. No development times were observed among field strain at 32°C and 34°C. The wing length of female of both strains was measured following the emergence of adult at each temperature treatment. It has been found that the wing length was inversely related to temperature. The mean wing length of field strain reared at higher temperature was found shorter (2.09 mm) than those reared under lower temperature (2.28 mm, p=O.OO 1). The same result was observed for laboratory strain where the mean wing length of female mosquito reared under higher temperature was found shorter (2.22 mm) than those reared at lower temperature (2.60 mrn, X2=23.23, df=3, p==O.OO 1). The outcomes of this study are discussed in the context of changing in water temperature and its influence on the development times and survival of Aedes albopictus which consequently may have an impact on the vectorial capacity ofthis mosquito.